Antimicrobial activity and prebiotic effects of senna alata leaf extracts - Zakaria, Nik Hasanah (2022)
Senna alata or Cassia alata is a medicinal plant found mostly in the tropics and subtropics. The leaves of the plant have been employed in the treatment of skin infection and digestion-related problems. The purpose of this study was to assess the antimicrobial activity of S. alata leaf extracts against several intestinal pathogens and their prebiotic effects against a few probiotic strains, as well as to screen the phytoconstituents in S. alata leaf extracts. MIC and MBC assays of aqueous and ethanolic leaf extract in a concentration ranging from 0.39 mg/mL to 200 mg/mL were performed on the intestinal pathogens in a sterile 96-well microtiter plate. The prebiotic effects of aqueous and ethanolic leaf extracts in concentrations from 1.25 mg/mL to 10.00 mg/mL were evaluated based on the growth rate of the probiotic within 24 hours. The phytoconstituents of aqueous and ethanolic leaf extracts were screened by standard qualitative methods. Both leaf extracts showed a bactericidal effect against S. aureus, while only aqueous leaf extract showed a bacteriostatic effect against S. Typhi. Probiotics of L. helveticus and B. longum showed a positive mean growth rate after being treated with both leaf extracts for 24 hours. However, the growth rate of both bacteria decreases as the concentration of both leaf extracts increases. Both leaf extracts showed the presence of tannins, saponins, alkaloids, carbohydrates, and flavonoids. In conclusion, both S. alata leaf extracts showed significant antimicrobial activity against S. aureus and S. Typhi at the tested extract concentrations. Besides, both S. alata leaf extracts are weak prebiotics because they only stimulate a minimal growth of probiotics.